Diversitas dan Struktur Komunitas Kupu-kupu (Lepidoptera; Rhopalocera) di Hutan Riparian Sungai Wain Balikpapan: Diversity and Community Structure of Butterflies (Lepidoptera; Rhopalocera) in the Riparian Forest of Sungai Wain Balikpapan - Handiargo, Ferdy; Budiman, Budiman; Hariani, Nova (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study aims to examine the diversity and community structure of butterflies in the riparian forest vegetation type of the Sungai Wain Protected Forest Area, Balikpapan. The research was conducted using an exploratory-descriptive approach with a transect line method during morning and afternoon observations. A total of 329 individual butterflies representing 33 species were recorded, with Graphium evemon, Eurema sp., and Cupha erymanthis being the most frequently observed species and having the highest Important Value Index (IVI). The diversity index was 2.698. The dominance index was 0.0998, while the evenness index was 0.9002. The community similarity index between morning and afternoon in the riparian forest was 88%.